2015
DOI: 10.1007/s00430-014-0385-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multiplex PCR on antimicrobial treatment in febrile neutropenia: a randomized controlled study

Abstract: Multiplex PCR (mPCR) directly from blood has been suggested as a promising method for rapid identification of pathogens causing sepsis. This study aimed to investigate whether mPCR has any impact on antimicrobial treatment. Hematological patients with febrile neutropenia were randomized into two groups. In the study group, mPCR was performed as an addition to standard diagnostics, and PCR finding was immediately communicated to the clinicians, thus being available for decision making. In the control group, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…45,69,[71][72][73][74][75][76][77][78][80][81][82][83][85][86][87][90][91][92][93][94][96][97][98][99][101][102][103]107,[109][110][111][112]114 Of these, nine studies reported blood volumes that did not comply with CE approval: Lehmann et al, 76 Lodes et al 92 and von Lilienfeld-Toal et al 71 all reported using 1 ml in adults; Bloos et al, 74 Lamoth et al, 75 Paolucci et al 99 and Sitnik et al 107 all reported using 3 ml in adults; Berger et al…”
Section: Details Of Index and Reference Tests Blood Sampling Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…45,69,[71][72][73][74][75][76][77][78][80][81][82][83][85][86][87][90][91][92][93][94][96][97][98][99][101][102][103]107,[109][110][111][112]114 Of these, nine studies reported blood volumes that did not comply with CE approval: Lehmann et al, 76 Lodes et al 92 and von Lilienfeld-Toal et al 71 all reported using 1 ml in adults; Bloos et al, 74 Lamoth et al, 75 Paolucci et al 99 and Sitnik et al 107 all reported using 3 ml in adults; Berger et al…”
Section: Details Of Index and Reference Tests Blood Sampling Methodsmentioning
confidence: 99%
“…community, emergency department, hospital, intensive/critical care, general/ specialist) was not reported for nine SeptiFast studies, 44,65,69,72,88,98,100,105,110 or for one multitest SeptiFast and SepsiTest study 118 (confidential information has been removed). The setting across the remaining studies varied (see Table 4).…”
Section: Study Design Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…56 Whether application of these diagnostic methods has a measurable impact on HCT patient outcomes remains to be elucidated. 57 Role of surveillance blood cultures A retrospective study of asymptomatic adult allo-HCT recipients with CVCs who had 6801 surveillance blood cultures performed showed surveillance cultures infrequently yielded significant results (0.59% of all surveillance blood cultures drawn) and were associated with unnecessary medical interventions and added cost. 58 A prospective observational study in allo-HCT recipients receiving steroids who underwent daily blood culture surveillance also did not demonstrate a clear benefit and rarely identified a CLABSI.…”
Section: Microbiological Detection Of Bloodstream Infections In Hct Pmentioning
confidence: 99%